BEYOND FINANCIAL REPORTING QUALITY: DIGITAL TRANSFORMATION AND PUBLIC VALUE IN LOCAL GOVERNMENT ACCOUNTING - Gustita Arnawati Putri; Yoga Pratama Nugroho; Ahmad Dzakiyuddin (Jurnal Akuntansi, 2026)
Digital transformation has become a central strategy forreforming public sector accounting, yet its ultimate contributionto society is often assessed narrowly through the lens offinancial reporting quality alone. This study argues thatfinancial reporting quality, while necessary, is not sufficient tocapture the broader societal contribution of digital reform, andtherefore examines how Digital Transformation affects PublicValue in local government, both directly and indirectly throughFinancial Reporting Quality as a mediating variable. Evidencefrom Indonesian local governments shows that although theRegional Government Information System (SIPD-RI) has beenadopted almost universally, improvements in financialstatement quality have not consistently translated into greaterpublic trust, service responsiveness, or perceived governmentallegitimacy. This study employs a quantitative explanatorysurvey design involving 200 respondents, comprising financialofficers and public service managers in Regional ApparatusOrganizations (OPD), selected through purposive sampling.Data were analyzed using IBM SPSS Statistics through validitytesting, reliability testing, classical assumption testing, multiplelinear regression, and mediation analysis using the causal-stepsapproach complemented by the Sobel test. The results show thatDigital Transformation has a positive and significant effect onboth Financial Reporting Quality and Public Value, FinancialReporting Quality positively affects Public Value, and FinancialReporting Quality partially mediates the effect of DigitalTransformation on Public Value. These findings extend PublicValue Theory and Institutional Theory by demonstrating thatdigital reform generates societal value through paralleltechnical and legitimacy-based pathways, offering practicalimplications for local governments seeking to move beyondcompliance-oriented digitalization toward genuine public valuecreation